(untitled) (American Journal of Islam and Society, 2009)
Taking an expansive notion of what is a “veil” and recognizing its immemorial relationship to sacredness, Jennifer Heath has put together a wonderful collection of essays about it. The twenty-one female contributors consider the veil from a variety of viewpoints: academic, personal memoir, and artistic. Her introduction and epilogue presents the book’s overall goal and a summation. The main argument is that “the veil” has been (and will remain) part of human society, in countless cultures and religions, for thousands of years. It can be a piece of cloth, a mask, or even related to the mystery of nature (as in the ancient Greek goddess Nyx [Night], drawing the veil of darkness across earth, while Selene [Moon] rises wearing a veil [p. 5].).” Current debates over veiling focus only on Islamic veiling and its relationship to women’s oppression, which politicizes and narrows the understanding of this practice. There is no singular truth to “the veil,” Heath suggests, and that is precisely the feeling one gets, for after reading the entire collection, one is no wiser to “the” meaning of “the” veil. The “truth” of the veil, rather, is that the current debate over it (does it or does it not oppress women?) detracts from the real issues women face: ...